Problematika Penerapan Metode Course Review Horray Pada Pembelajaran Bahasa Arab - Jalaludinfaruk; Asyhari; Nisa', Nur Imamatun (STAI Nurul Huda Kapongan Situbondo, 2024)
Learning Arabic requires that each individual instructor understand components that are inextricably linked to learning outcomes, such as instructional methods, media, and competences. Arabic language instructors at MTsN 02 Pamekasan have not adequately implemented effective learning methodologies. This, of course, causes pupils to lose excitement during the learning process, affecting their learning outcomes. To resolve this issue, extensive activity is necessary, namely the Course Review Horay Method. This research study employs a qualitative approach and includes a case study. The problems in implementing the course review horray approach for students' Arabic language learning led to several results, including the following: there was no perception or motivation during the preparation stage. The implementation stage included effective teaching time, a vibrant classroom environment, regular teacher explanations, and opportunities for students to cheat. At the evaluation stage, aggressive and quiet pupils from the same group received similar evaluations.